The metacognitive training of future professionals in higher education: the experience of implementation and peculiarities - Adonieva, Yuliia (ScienceRise: Pedagogical Education, 2017)
In the research was realized the analysis of metagognitive training programs, realized in the process of professional training of future specialists in higher educational institutions. There were determined scientific-methodological grounds of the successful formation of metacognitions as complicated, multi-level and system-organized psychical formations that have the procedural and autonomously developed form, are directed on the organization, regulation and coordination of primary cognitive processes and provide the general regulation of the training and professional activity of future specialists. In the paper is noted that effective metacognitive training programs for future specialists in HEIs: – must be supported by the motivation, students’ interest; must include the theoretical part that provides the mastering of metacognitive knowledge by students and the practical one that provides metacognitive skills formation; – must provide the reflection and students’ reflexive skills development; – be realized with the support on regulative processes; – Must take into account unevenness and heterogeneity of the mastering, fixation and generalization of different metacognitive skills; – must be grounded on the specificity of an individual and collective activity; – must provide the use of written supports, schemes that give a possibility to visualize the process of a task solution